2016
DOI: 10.4049/jimmunol.1502136
|View full text |Cite
|
Sign up to set email alerts
|

The Emerging Importance of IgG Fab Glycosylation in Immunity

Abstract: Human IgG is the most abundant glycoprotein in serum and is crucial for protective immunity. In addition to conserved IgG Fc glycans, ∼15–25% of serum IgG contains glycans within the variable domains. These so-called “Fab glycans” are primarily highly processed complex-type biantennary N-glycans linked to N-glycosylation sites that emerge during somatic hypermutation. Specific patterns of Fab glycosylation are concurrent with physiological and pathological conditions, such as pregnancy and rheumatoid arthritis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
226
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 255 publications
(236 citation statements)
references
References 82 publications
10
226
0
Order By: Relevance
“…It has been estimated that up to 10 -25% of healthy donor IgG molecules carry Fab-linked N-glycans (8). In line with this, our current data indicate that plasma and SF IgG (depleted of ACPA) of RA patients exhibit a median level of Fab-glycosylation of around 17%, albeit with variation between donors.…”
Section: Acpa-igg Exhibit a Higher Level Of Fab Glycosylation-wesupporting
confidence: 88%
See 3 more Smart Citations
“…It has been estimated that up to 10 -25% of healthy donor IgG molecules carry Fab-linked N-glycans (8). In line with this, our current data indicate that plasma and SF IgG (depleted of ACPA) of RA patients exhibit a median level of Fab-glycosylation of around 17%, albeit with variation between donors.…”
Section: Acpa-igg Exhibit a Higher Level Of Fab Glycosylation-wesupporting
confidence: 88%
“…Next to Fc-glycosylation, we have recently reported that ACPA-IgG are extensively glycosylated in their variable domain; a feature that may modulate the function of ACPA-IgG and that could be involved in the pathophysiology of RA (8). So far, however, a detailed structural analysis of ACPA Fablinked glycans was lacking (13).…”
Section: Acpa-igg Exhibit a Higher Level Of Fab Glycosylation-wementioning
confidence: 99%
See 2 more Smart Citations
“…The importance of this type of glycosylation is underscored by its ability to modulate IgG antigen binding and affect the anti-inflammatory properties of IVIG. 34 Another challenging type of glycosylation present in a variety of immunoglobulins, O-glycosylation, 35 is especially hard to predict because a consensus amino acid sequence motif has not been identified. Therefore, new methods that can better characterize the presence of these challenging glycosylation varieties are warranted.…”
Section: Discussionmentioning
confidence: 99%